Pendampingan Baca Al-Qur’an: Penyelenggaraan Kegiatan Tahsin Tilawah Al-Qur’an Sebagai Upaya Penyempurnaan Bacaan Al-Qur’an Santri - Muhammad Nabil Akmal; Muhammad Yusron Maulana El-Yunusi; Rommy Hardyansah; Arif Rachman Putra; Didit Darmawan; Eli Masnawati; Mila Hariani (Lembaga Pengembangan Kinerja Dosen, 2024)
Al-Qur'an recitation assistance at TPQ Saroja Kutisari Tenggilis Mejoyo, Surabaya, is key in improving the quality of Al-Qur'an recitation among students. This research explores the implementation of Tahsin Tilawah Al-Qur'an activities as a step to perfect the recitation of the Al-Qur'an in the neighborhood. Through a qualitative method with participatory observation, the results show that this activity is effective in improving the recitation of the Qur'an of the students. Factors such as direct guidance from the ustadz, a conducive learning atmosphere, and interaction between fellow students play an important role in the success of this program. This research provides an in-depth understanding of the role of Qur'an recitation mentoring in religious education in Indonesia, as well as making important contributions to the development of similar programs in the future.